Data Analysis and Predictive Modelling on Heart Disease based on People’s Lifestyle - Leonardo, Edward; Velayutham, Murugananthan; Gilbert, Justin (EAI Endorsed Transactions on Pervasive Health and Technology, 2024)
Coronary Artery Disease (CAD) is a form of heart disease primarily influenced by lifestyle choices. Despite preventative measures available to mitigate CAD risks, a significant proportion of the population remains unaware of its severity and consequently neglects necessary precautions. As a result, the influence of CAD continues to rise. This project aims to curb CAD cases by developing an early warning detection and educational accessible to the general population, leveraging Machine Learning and Data Visualization technologies. Research indicates that while Coronary Artery Disease can be mitigated through a lifestyle shift towards healthier living, the risk remains due to factors such as age and natural health deterioration.
Keywords: Coronary Artery Disease; Heart Disease; Machine Learning; Predictive Modelling; Data Analysis